Study of the capacity of bacterial species isolated from oil contaminated marine sediments cores to colonize and produce biofilm on virgin PE and PET microplastics under controlled marine environment - Rodríguez-Cordero, Stephanny María (Instituto Tecnológico de Costa Rica, 2021)
From the estimated 5.25 trillion floating plastic particles in the ocean, 92% are microplastics (MPs). Their surfaces can be colonized by bacteria, which make these polymers potential vectors for the dispersion of pathogens through marine environment and high food chains. This study shows results of the ability of bacterial isolates from marine sediments to colonize PE and PET MPs under controlled marine environment. The presence of presumptive Vibrio parahaemolyticus was examined by TCBS and the biofilm production capacity was determined by Congo red agar and Crystal violet tests. MPs were analyzed under SEM and the species identification was carried out by qPCR, PCR and DNA sequencing. No V. parahaemolyticus were present in the analyzed samples and only 22% of the total samples were positive in both CV and CRA tests. However, both PE and PET MPs exhibited bacterial adhesion in all sequenced samples, and PE presented the highest biofilm production. It was determined for the first time the biofilm production capacity of M. yunnanensis, V. dokdonensis, B. flexus and the presumptive F. arsenicus and F. nanhaiensis on both polymers. In addition to B. safensis ability to produce biofilm on PE, B. pumilus attachment to PET and the biofilm production capacity of the presumptive B. aquamaris and B. vietnamensis on PE. These new findings may serve as an insight for future studies regarding the ability of the identified species to colonize MPs under marine environment, which might represent a possible risk due to their high persistence and potential pathogenicity.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Química, 2021.
Esta tesis cumple con el objetivo ODS 14: conservar y utilizar sosteniblemente los océanos, los mares y los recursos marinos para el desarrollo sostenibles. Meta a: aumentar los conocimientos científicos y desarrollar la capacidad de investigación para transferir tecnología marina, teniendo en cuenta los Criterios y Directrices para la Transferencia de Tecnología Marina de la Comisión Oceanográfica Intergubernamental, a fin de mejorar la salud de los océanos y potenciar la biodiversidad marina al desarrollo de los países en desarrollo, en particular los pequeños Estados insulares y los países menos adelantados.
Keywords: Capacidad de especies bacterianas; Sedimentos marinos; Contaminación del agua; Petróleo; Microplásticos; Contaminación plástica; Polietileno (PE); Bacterias; Polietileno tereftalato; Biofilms; Polímeros; Dispersión -- Patógenos; Bacterial species capacity; Marine sediments; Water pollution; Petroleum; Water contamination; Microplastics; Plastic contamination; Bacterial; Polyethylene terephthalate; Polymers; Spread -- Pathogens; Research Subject Categories::TECHNOLOGY::Chemical engineering; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering